Juvenile Nile Tilapia fed different levels of protein hydrolysate from poultry liver (Research, Society and Development, 2024)
The objective of the present work was to evaluate the growth of juvenile Nile tilapia (9.38g ± 0.22g) fed with different increasing levels of protein hydrolysates from poultry liver. 500 fish were distributed in 25 tanks with a useful water volume of 450 liters (20 fish per tank), submitted to different diets containing varying levels of poultry liver protein 0 (control); 1.5; 3.0; 4.5 and 6.0%. Statistically significant differences (p ≤ 0.05) were evident in the parameters of final weight, weight gain, feed consumption and final length, with better zootechnical performance in animals fed with hydrolyzed diets. The results demonstrate the effectiveness of using poultry liver protein hydrolyzate due to its nutritional value in formulating feed for juvenile Nile tilapia. Based on the results obtained, it is recommended that 1.5% of poultry liver protein hydrolyzate be included in diets for juvenile Nile tilapia.